2014
DOI: 10.1016/j.pain.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

HCN2 channels account for mechanical (but not heat) hyperalgesia during long-standing inflammation

Abstract: There is emerging evidence that hyperpolarization-activated cation (HCN) channels are involved in the development of pathological pain, including allodynia and hyperalgesia. Mice lacking the HCN isoform 2 display reduced heat but unchanged mechanical pain behavior, as recently shown in preclinical models of acute inflammatory pain. However, the impact of HCN2 to chronic pain conditions is less clear and has not been examined so far. In this report, we study the role of HCN2 in the complete Freund's adjuvant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 50 publications
5
82
4
Order By: Relevance
“…However, contrary to this previous report, a more recent paper suggests that this subtype is not responsible for inflammation-induced heat hypersensitivity (Schnorr et al, 2014). Based on these findings, it seems likely that the reversal of heat hypersensitivity by ZD7288 in the neuritis model is due to blockade of multiple channels, which may also include other HCN subtypes.…”
Section: Role Of the Hcn2 Subtypecontrasting
confidence: 82%
See 1 more Smart Citation
“…However, contrary to this previous report, a more recent paper suggests that this subtype is not responsible for inflammation-induced heat hypersensitivity (Schnorr et al, 2014). Based on these findings, it seems likely that the reversal of heat hypersensitivity by ZD7288 in the neuritis model is due to blockade of multiple channels, which may also include other HCN subtypes.…”
Section: Role Of the Hcn2 Subtypecontrasting
confidence: 82%
“…Following CCI, there is a decrease in the expression of HCN2 within the DRG and a redistribution of the channel proximal to the injury site (Jiang et al, 2008). Consistent with a role for this isoform in neuropathic pain mechanisms, deletion of HCN2 from nociceptive neurons has been shown to prevent the development of pain behaviors in the CCI model and following inflammation of the hind paw (Emery et al, 2011;Schnorr et al, 2014).…”
Section: Introductionmentioning
confidence: 80%
“…Of the four isoforms of the HCN channels (HCN1-4), HCN2 is believed to play a pivotal role in chronic pain on the basis that: (a) deletion of HCN2 in nociceptive neurons prevented the development of pain behaviors in the CCI model and inflammatory pain models (Emery et al, 2011;Schnorr et al, 2014, see also Emery et al, 2012 for review) and (b) HCN2 expression was increased in small DRG neurons following chronic hindlimb inflammation (Weng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since most of the proteins that are expressed in the somata of primary afferent (DRG) neurons are also expressed in their free nerve endings and in their central and peripheral axonal branches (see Basbaum et al, 2009), it is possible that changes in HCN expression in the somata of DRG neurons may also occur in their peripheral terminals. Changes in expression and/or function of HCN channels at peripheral nerve terminals may result in a lowered threshold and/or a greater gain of the stimulus-response relationship (Schnorr et al, 2014) and may also contribute to SA generation and thereby to PNP.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that HCN2 channels play a central role in inflammatory and neuropathic pain [43,44,45]. Zhou et al [46] indicated that HCN channels may contribute to regional anesthetic effects of lidocaine.…”
Section: Discussionmentioning
confidence: 99%